Three professional dilemmas of czech newspaper editors: twenty years after collapse of old media system - Volek, Jaromír (Communication Today, 2025)
Czech newspaper editors feel a strong inner professional confl ict concerning following professional dilemma: to be a moral agent focused on serious problems of society or a craftsman who has generally given up on higher standards of journalistic work and tries to conform to popular standard of general audience. The presented paper is based upon the research project – “Czech newspaper editors” which was undertaken between June-August 2007. The main objective of this study was to show how Czech newspaper editors changed their editorial strategy after the collapse of the former media system in the 1990s and to what extent they have adapted to the pressure of economic rationalization and the commercialization of the media sector. The second objective was to describecriteria that editors instinctively use to evaluate what readers want to consume.